Proses Pembentukan Citra Diri Melalui Media Sosial Instagram (Studi Kasus Pada Akun Selebgram @Roro_Yustina): Proses Pembentukan Citra Diri Melalui Media Sosial Instagram (Studi Kasus Pada Akun Selebgram @Roro_Yustina) - Nurul Aulia; Desi Yunita; Wahyu Gunawan (UNIB Press, 2024)
The process of forming a self-image on Instagram social media is called impression management, which is formed to give a positive impression to other people. This research uses a qualitative research method with a descriptive approach and focuses on the process of forming a self-image on Instagram social media using Erving Goffman's dramaturgical theory. This qualitative research uses a case study method by investigating how the process of @Roro_yustina's account as a celebrity forms her image through her Instagram social media account, with technical interviews to obtain data results. The results of this research show that the process of forming one's self-image on social media is very important, especially on social media, because the first thing the public sees is one's self-image, which can influence other people's first impressions. Roro Yustina, as a program celebrity, succeeded in forming a good self-image for the first time by carrying out self-presentation and impression management in accordance with the concept of dramaturgical theory. This is done in a way that Roro Yustina can maintain and control the impression given to her followers. Apart from that, using Erving Goffman's theory, especially front stage and back stage, it can be seen that Roro Yustina, as a celebrity, only shares positive things with her followers; on the other hand, there are some things that are not shared, such as her personal life and attitude on stage. behind or backstage